Validating 3D two-parameter fracture mechanics models for structural integrity assessments. (October 2019) - Simpson, C.A.; Tonge, S.; Connolley, T.; Reinhard, C.; Marrow, T.J.; Mostafavi, M.
Highlights: High energy X-rays facilitate the detailed study of 3D plastic constraint. Through thickness strain variation and measurement averaging must be considered. Finite element facture analysis relies on due consideration of crack tip blunting. Unrealistically sharp meshes lead to severe overestimates of near crack tip strains. Abstract: In-situ fracture tests were carried out on the I12 beamline at the Diamond Light Source. Four Al-Ti metal-matrix composites, with two crack lengths, were studied to assess for the impact of in-plane constraint. Synchrotron X-ray computed tomography and synchrotron X-ray diffraction were used to measure total strain and elastic strain respectively. In this work, the measured elastic strains in the samples are detailed as a function of applied load and compared against those predicted from a 3D elastic-plastic finite element model. The modelled strains increased asymptotically towards the tip of the electro discharge machined notch. The experimental results do not highlight the same response, which is due to a combination of blunting and low experimental spatial resolution. Far field experimental and measured strain fields converged, notably in the test piece containing a long notch ( a / W = 0.5) and higher levels of constraint.